Variant cell lines selected for alterations in the function of the hyaluronan receptor CD44 show differences in glycosylation (The Rockefeller University Press, 1995)
CD44 is a major cell surface receptor for the extracellular matrix glycosaminoglycan hyaluronan (HA). However, the ability of CD44 to bind ligand is strictly regulated. Three activation states of CD44 have been demonstrated: (a) inactive; (b) inducible (by certain CD44-specific mAb); and (c) constitutively active. Starting with two parental cell lines expressing CD44 in the inactive state, a pre-B cell (RAW 253) and a fibroblast (L cells), we used fluorescence-activated cell sorting with fluorescein-conjugated hyaluronan in the presence of inducing mAb to derive variant cell lines with CD44 in the inducible state. Constitutively active derivatives were isolated from the inducible variants by a further round of fluorescence-activated cell sorting in the absence of inducing antibody. However, constitutively active variants could not be isolated directly from parental cells expressing CD44 in the inactive state. These results suggest that two genetic events must occur to obtain an active CD44-HA receptor from an inactive receptor. Variant and parental cell-derived CD44 molecules exhibited differences in migration on sodium dodecyl sulfate-polyacrylamide gel electrophoresis that were partly attributable to differences in N- linked glycosylation. Furthermore, culture in tunicamycin for 2-3 d converted parental and inducible cell lines into cells showing constitutive CD44-mediated HA binding. Also, removal of cell surface glycosaminoglycan chains by culture of cells in p-nitrophenyl beta-D- xylopyranoside or treatment with chondroitinase ABC resulted in conversion of cells with an inactive CD44 receptor to an inducible state. These results indicate that carbohydrate side chains of CD44 and/or other molecules on the cell surface that interact with CD44 are potentially involved in regulating the HA-binding function of CD44 on the cell surface.